Influence of the transition from symmetric to asymmetric fission mode on the average total kinetic energy and neutron multiplicity - Pasca H. Horia; Andreev A. V. Aleksandr Vasiljevich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich (2023, 2023)
For the electromagnetic-induced fission of even 222–230Th isotopes, the effect of the transition from a symmetric fission mode to an asymmetric one on the charge/mass, total kinetic energy, neutron multiplicity distributions, and probability for a given neutron multiplicity per fission event is explored within an improved scission-point model. The simultaneous description all these observables and correlations between them are presented.